Descrição da geração eólica com ênfase nos requisitos de qualidade de energia e proteção elétrica da turbina - Camilo Assunção Silveira (2017)
The aim of this work starts from the history of the wind generation, its expansion, technologies and challenges. The following are explored ways of calculating mechanical wind power, their maximum effiiciency, the definition of the capacity factor for the electrical energy produced, the constructive aspects and the amin equipment that form a wind turbine according to current market technologies. Highlight wil be given to wind turbines with DFIG technology - Doubly Fed Induction Generator in conjunction with back-to-back power converters, their sub-synchronous and hyper-synchronous modes of operation for different wind speeds as well as the ratio of the generator slip to the converter power dimensioning. The first main theme of this work will detail the power quality requirements to be met by the wind farm as requested by the ONS and applicable international technical standards, as well as actual results of power quality measurements campaigns for a wind farm located in the northeast of Brazil. The requirements for connection of the wind farm to the grid are mainly present in the ONS standards [27] [30] [31] and in the international standard IEC 61400-21 [19]. In the end a new harmonic current distortion identification algorithm will be proposed in the wind turbine classifying it as coming from the external grid or in the turbine itself. The second main theme of the dissertation is the electrical protection of the wind turbine in its medium voltage zone. It is approached a coordination and selectivity next to the substation of the wind farm that connects to the basic network, as well as a new proposal of electrocaç fault identification in the medium voltage. It is proposed through this dissertation to store a database for the first year of operation of the wind farm with fractal dimensional values and lacunarity of the partial discharges and the fifth order harmonic distortion. Through yhe obtained results it is proposed to create three rules for the classification of the type of electrical fault. The action to be performed may involve planned maintenance or stop immediately the operarion of this wind turbine